2021
DOI: 10.1002/er.6937
|View full text |Cite
|
Sign up to set email alerts
|

Space degradation of triple junction solar cells at low temperatures: II ‐electron irradiation

Abstract: We investigated the behavior of electron-irradiated 3G28 InGaP/GaAs/Ge triple junction solar cells and their component (top, middle and bottom) cells at low temperatures from 100 to 300 K and low illumination intensity. Significant degradation of their performances has been observed. We found that it is induced by an excess current associated with tunneling due to the presence of the radiation-induced defects introduced in the junctions of each sub-cell. The amount of tunneling current, hence of the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…To confine the misfit dislocation and minimize the strain, the previous study reported 6 that multijunction (MJ) III‐V devices use compositionally graded buffers, which have demonstrated solar‐to‐electrical conversion efficiency of 39.2% (1 sun AM1.5G). The Ge‐based III‐V TJ solar cells of the various bandgap combination (ie, to absorb various color band ranges of the solar spectrum) display high efficiencies 7‐9 . A number of Ge‐based III‐V TJ solar cell concepts 8,10,11 are studied by research groups around the world in order to improve the conversion efficiency and reduce devices cost.…”
Section: │ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To confine the misfit dislocation and minimize the strain, the previous study reported 6 that multijunction (MJ) III‐V devices use compositionally graded buffers, which have demonstrated solar‐to‐electrical conversion efficiency of 39.2% (1 sun AM1.5G). The Ge‐based III‐V TJ solar cells of the various bandgap combination (ie, to absorb various color band ranges of the solar spectrum) display high efficiencies 7‐9 . A number of Ge‐based III‐V TJ solar cell concepts 8,10,11 are studied by research groups around the world in order to improve the conversion efficiency and reduce devices cost.…”
Section: │ Introductionmentioning
confidence: 99%
“…The Ge-based III-V TJ solar cells of the various bandgap combination (ie, to absorb various color band ranges of the solar spectrum) display high efficiencies. [7][8][9] A number of Ge-based III-V TJ solar cell concepts 8,10,11 are studied by research groups around the world in order to improve the conversion efficiency and reduce devices cost. But, until now, it cannot be widely adopted in the field of civilian application due to its toxicity, poor mechanical properties, the limited abundance of III-V elements in earth, and so on.…”
Section: │ Introductionmentioning
confidence: 99%
“…3 Nowadays, the new generation solar cells for space applications are facing increasingly severe radiation environments during interstellar missions and deep space exploration. 3,4 Therefore, understanding solar cell degradation behavior under different irradiation environments is exceedingly important for precise evaluation of solar cell lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…However, solar cells serving in‐orbit satellites and aircraft suffer from high‐energy radiation particles in space environment, and these particles shorten the minority carrier lifetime by generating non‐radiative recombination centers in solar cell materials, and, eventually, lead to degradation of overall cell performance 3 . Nowadays, the new generation solar cells for space applications are facing increasingly severe radiation environments during interstellar missions and deep space exploration 3,4 . Therefore, understanding solar cell degradation behavior under different irradiation environments is exceedingly important for precise evaluation of solar cell lifetime.…”
Section: Introductionmentioning
confidence: 99%